Dynamic Economic Models: The Derivational Steps of Time Path with Numerical Example (Lapai Journal of Economics, 2021)
Studies that explain the derivation of the general solution formula of time path in dynamic economic models are fragmented, with some explanations found in economics, mathematics and physics. This creates phobia among economists on the dynamic concept, with many economists only applying the dynamic formula without comprehending the intricacies involved in its derivation. The result of this may be the wrong application of the formula or inability to make good interpretation. This paper has applied the most elementary approach in exploring the derivational steps of dynamic economic models using micro economics examples (time path of price).